The Value of Innovation: The Interaction of Competition, R&D; and IP. - Greenhalgh, C; Rogers, M (2006)
This paper analyses market valuations of UK companies using a new data set of their R&D; and IP activities (1989-2002). In contrast to previous studies, the analysis is conducted at the sectoral-level, where the sectors are based on the technological classification originating from Pavitt [Pavitt, K., 1984. Sectoral patterns of technical change. Research Policy 13, 343-373]. The first main result is that the valuation of R&D; varies substantially across these sectors. Another important result is that, on average, firms that receive only UK patents tend to have no significant market premium. In direct contrast, patenting through the European Patent Office does raise market value, as does the registration of trade marks in the UK for most sectors. To explore these variations the paper links competitive conditions with the market valuation of innovation. Using profit persistence as a measure of competitive pressure, we find that the sectors that are the most competitive have the lowest market valuation of R&D.; Furthermore, within the most competitive sector ("science based" manufacturing), firms with larger market shares (an inverse indicator of competitive pressure) also have higher R&D; valuations, as well as some positive return to UK patents. We conclude that this evidence supports Schumpeter by finding higher returns to innovation in less than fully competitive markets and contradicts Arrow [Arrow, K., 1962. Economic welfare and the allocation of resources for invention. In: Nelson, R. (Ed.), The Rate and Direction of Inventive Activity. Princeton University Press, Princeton], who argued that, with the existence of IP rights, competitive market structure provides higher incentives to innovate.